KULIAH ENTREPRENEURSHIP DAN RELEVANSINYA TERHADAP SEMANGAT BERWIRAUSAHA MAHASISWA FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN ANTASARI BANJARMASIN - Hafizah, Yulia (At-Taradhi, 2014)
This paper is the description of student response towards learning of enterpreneurshipthat they get in Sharia faculty dan Islamic economy. Besides, it talks about effect of the learning towards their interest in entrepreneurship. The result is education and curriculum of enterpreneurship in campus that constitute manifestation from embodiment of CollegeTri Dharma have function to supply the students with the knowledge of entrepreneurship as well as able to change their point of view to business world. Students interest in entrepreneurship are growing and developing in line with the increasingly widespread planting of entrepreneurial spirit among them.